Genetic risk factors for osteochondrosis in various horse breeds. (30th March 2018) - Naccache, F.; Metzger, J.; Distl, O.
Summary: Osteochondrosis (OC) is an injury to cartilage canals with a following necrosis in the growth cartilage, from there it can develop to osteochondrosis dissecans (OCD). Due to its high impact in the equine industry, new insights into predisposing factors and potential high‐risk genetic variants are warranted. This article reviews advancements in quantitative and molecular genetics in refining estimation of genetic parameters and identifying predisposing genetic loci. Heritabilities were highest for hock OC with estimates at 0.29–0.46 in Hanoverian warmblood and Norwegian trotters, whereas in Thoroughbreds only very low genetic variation seemed to be present in hock OC lesions. Whole genome scans using the Illumina Equine SNP50 or SNP70 Beadchip were performed in Thoroughbred, Standardbred, French and Norwegian trotter, Hanoverian and Dutch warmblood. Validation studies in Spanish Purebred and Hanoverian warmblood horses corroborated OC risk loci on ECA 3, 14, 27 and 29. Particularly, a strong association with hock‐OCD was found for a single nucleotide polymorphism (SNP) on horse chromosome (ECA) 3 upstream to the LCORL gene. Gene expression and microRNA analyses may be helpful to understand pathophysiological processes in equine OC and to connect OCD‐associated genomic regions with potential candidate genes. Furthermore progress in elucidating the underlying genetic variants and pathophysiological changes in OC may be expected from whole genome DNA and RNA next‐generation sequencing studies.